2016
DOI: 10.3390/e18040108
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Supersymmetric Theory of Stochastics

Abstract: Many natural and engineered dynamical systems, including all living objects, exhibit signatures of what can be called spontaneous dynamical long-range order (DLRO). This order's omnipresence has long been recognized by the scientific community, as evidenced by a myriad of related concepts, theoretical and phenomenological frameworks, and experimental phenomena such as turbulence, $1/f$ noise, dynamical complexity, chaos and the butterfly effect, the Richter scale for earthquakes and the scale-free statistics o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 126 publications
(180 reference statements)
0
91
0
Order By: Relevance
“…[6] The TE state is (one of) the ground state(s) of the DS with the Langevin potential playing the role of the Lyapunov function,…”
Section: Chaotic and Thermal Annealing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] The TE state is (one of) the ground state(s) of the DS with the Langevin potential playing the role of the Lyapunov function,…”
Section: Chaotic and Thermal Annealing Methodsmentioning
confidence: 99%
“…The recently found approximation-free STS [6] lays at the heart of the proposition in this paper and we would like to begin with a brief discussion of this theory. The easiest way to address the STS is to consider the following class of SDEs that covers most of the models in the literature,ẋ…”
Section: General Phase Diagram Of Stochastic Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…75 This analogy is not far-fetched since it has been shown that any classical dynamical system (with and without noise) can be expressed within a topological field theory. 72 The topological field theory that emerges is of a Witten type. 76 Therefore, any transient dynamics can be described within the same instantonic formalism, where, of course, the critical points, and the topological sector of the theory change according to the physical system considered.…”
Section: Instantonsmentioning
confidence: 99%
“…(3) in a path-integral representation, 71 the partition function of such representation has an action functional, S Eucl , which is of topological character. 72 As any physical system, the trajectory chosen by the system is the one that renders such action functional stationary. 73 Instantons turn out to be those trajectories that render the topological S Eucl stationary 69,70 dS Eucl ðx cl ðt; rÞÞ ¼ 0:…”
Section: Instantonsmentioning
confidence: 99%